2020
DOI: 10.3389/fimmu.2020.00183
|View full text |Cite
|
Sign up to set email alerts
|

The Methyl-CpG-Binding Protein Mbd2 Regulates Susceptibility to Experimental Colitis via Control of CD11c+ Cells and Colonic Epithelium

Abstract: Methyl-CpG-binding domain-2 (Mbd2) acts as an epigenetic regulator of gene expression, by linking DNA methylation to repressive chromatin structure. Although Mbd2 is widely expressed in gastrointestinal immune cells and is implicated in regulating intestinal cancer, anti-helminth responses and colonic inflammation, the Mbd2expressing cell types that control these responses are incompletely defined. Indeed, epigenetic control of gene expression in cells that regulate intestinal immunity is generally poorly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…Interestingly therefore, the suppression of DC maturation, particularly in terms of TLR signalling, by total excretory-secretory products released by the parasitic trematode worm Fasciola gigantica (FgESPs) has recently been shown to be associated with changes in the methylome and transcriptome reprogramming [ 59 ]. Moreover, the methyl-CpG-binding protein, Mbd2, that acts to coordinate chromatin accessibility and hence, reprogramming of gene expression in response to DNA methylation, is key to the ability of DCs to drive Th2 responses to helminths and allergy [ 60 ] and also plays a role in CD11c + DC/monocyte-epithelial cell crosstalk in gut inflammation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly therefore, the suppression of DC maturation, particularly in terms of TLR signalling, by total excretory-secretory products released by the parasitic trematode worm Fasciola gigantica (FgESPs) has recently been shown to be associated with changes in the methylome and transcriptome reprogramming [ 59 ]. Moreover, the methyl-CpG-binding protein, Mbd2, that acts to coordinate chromatin accessibility and hence, reprogramming of gene expression in response to DNA methylation, is key to the ability of DCs to drive Th2 responses to helminths and allergy [ 60 ] and also plays a role in CD11c + DC/monocyte-epithelial cell crosstalk in gut inflammation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly therefore, the suppression of DC maturation (buffalo cells), particularly in terms of TLR signalling, by excretory-secretory products released by the parasitic trematode worm Fasciola gigantica (FgESPs) has recently been shown to be associated with changes in the methylome and transcriptome reprogramming 96 . Moreover, the methyl-CpG-binding protein, Mbd2, that acts to coordinate chromatin accessibility and hence, reprogramming of gene expression in response to DNA methylation, is key to the ability of DCs to drive Th2 responses to helminths and allergy 97 and also plays a role in CD11c+ DC/monocyte-epithelial cell crosstalk in gut inflammation 98 . Although, exposure to ES-62 does not substantially impact on the methylation profile of Mbd2 in CIA-SFs, it results in TSS hypermethylation of Mbd3l2, a homologous protein that can also interact with components of the NuRD complex but to antagonize Mbd2-mediated methylation silencing 99, 100 , an inverse signature to that of naïve and CIA-SFs (hypomethylated).…”
Section: Discussionmentioning
confidence: 99%
“…S12 ). Less is known about MBD2 in macrophages, although it has been linked to intestinal inflammation in mice [44] and MBD2 deficiency has been associated with repressing the M2 macrophage programme in pulmonary fibrosis [45]. When we assessed the expression change upon infection with Salmonella for the genes in the IRF8 and MBD2 regulons, we observed that the IRF8 regulon is generally up-regulated upon infection, whereas the MBD2 regulon is mostly down-regulated ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…1I), which is in line with the typically scale-free structure of GRNs (32). The most connected TFs differ between the infected and the naive eGRN and include many well-established macrophage TFs such as IRF8, NFkB2, and RELB (33,34) and also less well established TFs such as MBD2, FOSL1 and NRF1, which have been implicated in macrophage biology in more recent studies in mice provide evidence for a role of MBD2, NRF1 FOSL1 in macrophages (3537).…”
Section: Resultsmentioning
confidence: 99%